Classroom Quality and Student Engagement: Contributions to Third-Grade Reading Skills - Guo, Ying; Connor, Carol M.; Tompkins, Virginia; Morrison, Frederick J. (Frontiers in Psychology, 2011)
This study, using NICHD Study of Early Child Care and Youth Development longitudinal data, investigated the effects of classroom quality and students’ third-grade behavioral engagement on students’ third-grade reading achievement (n = 1,364) and also examined the extent to which students’ third-grade behavioral engagement mediated the association between classroom quality and children's reading skills. SEM results revealed that controlling for family socio economic risk and students’ first-grade reading achievement, classroom quality significantly, and positively predicted children's behavioral engagement, which in turn predicted greater reading achievement. Higher levels of children's behavioral engagement were associated with higher reading achievement. Implications for policy and practice are discussed.